2021
DOI: 10.1071/rd21031
|View full text |Cite
|
Sign up to set email alerts
|

Sperm cryopreservation in an Australian skink (

Abstract: Assisted reproductive technologies for population and genetic management for threatened herpetofauna have grown substantially in the past decade. Here we describe experiments to optimise sperm cryopreservation in a model squamate, the eastern water skink Eulamprus quoyii. Small, concentrated volumes of highly motile spermatozoa were reliably collected from adult male E. quoyii by non-lethal ventral massage. Samples were used to: (1) test whether protein-rich diluents, namely Beltsville poultry semen extender (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…In the only other known test of Lake's solution as a diluent for cryopreservation in snakes, Zacarotti et al [23], found no post-thaw motility; however, Lake's was used in combination with the poorly performing CPA dimethyl sulfoxide (DMSO) at a low concentration (2 and 4%) [31]. We found that the extender mixture containing TEST yolk plus glycerol [29,67] conferred a similar recovery of viability as the CPA control mixture containing Lake's buffer with 10% DMF, 2% methanol, and 5% egg. We are not aware of any cryopreservation study that has used this combination of extender and CPA mixture to cryopreserve sperm of a species of snake other than the Louisiana pinesnake.…”
Section: Discussionmentioning
confidence: 66%
“…In the only other known test of Lake's solution as a diluent for cryopreservation in snakes, Zacarotti et al [23], found no post-thaw motility; however, Lake's was used in combination with the poorly performing CPA dimethyl sulfoxide (DMSO) at a low concentration (2 and 4%) [31]. We found that the extender mixture containing TEST yolk plus glycerol [29,67] conferred a similar recovery of viability as the CPA control mixture containing Lake's buffer with 10% DMF, 2% methanol, and 5% egg. We are not aware of any cryopreservation study that has used this combination of extender and CPA mixture to cryopreserve sperm of a species of snake other than the Louisiana pinesnake.…”
Section: Discussionmentioning
confidence: 66%
“…We note many sperm cryopreservation protocols developed to date have used sperm collected postmortem, due to the large quantities and quality of sperm obtained and the ease of protocol development this confers (Young et al 2017(Young et al , 2021(Young et al , 2022Campbell et al 2021aCampbell et al , 2021bSandfoss et al 2021). However, encouragingly, two recent studies have looked at sperm collected non-lethally, including the first study on tuatara (Lamar et al 2021;Hobbs et al 2022). We also believe that further studies on fundamental reptile reproductive ecology and physiology, along with testing fundamental hypotheses around cryopreserving reptile reproductive cells and tissues (Campbell et al 2021a) will aid with these conservation and research goals.…”
Section: Reptilesmentioning
confidence: 95%
“…The small number of published lizard protocols stands in stark contrast to the more than 6000 species of lizard worldwide that constitute half of all extant reptile species (Böhm et al 2013). The study by Hobbs et al (2022) extends the range of cryoprotectant and extender formulations available for lizards while recognising interactions between cooling rates and cryoprotectant type. The study by Campbell et al (2021b) demonstrates it is possible to cryopreserve sperm of the yellow-spotted monitor lizard Varanus panoptes after 4 days of cold-storage and still recover acceptable levels of motility (~30%) and plasma membrane integrity (~50%).…”
Section: Reptilesmentioning
confidence: 96%
See 1 more Smart Citation